2019
DOI: 10.1016/s0140-6736(19)32518-8
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan in Marfan syndrome (AIMS): a double-blind, placebo-controlled randomised trial

Abstract: SummaryBackgroundIrbesartan, a long acting selective angiotensin-1 receptor inhibitor, in Marfan syndrome might reduce aortic dilatation, which is associated with dissection and rupture. We aimed to determine the effects of irbesartan on the rate of aortic dilatation in children and adults with Marfan syndrome.MethodsWe did a placebo-controlled, double-blind randomised trial at 22 centres in the UK. Individuals aged 6–40 years with clinically confirmed Marfan syndrome were eligible for inclusion. Study partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 27 publications
(40 reference statements)
0
78
0
2
Order By: Relevance
“…Unfortunately, clinical data available on β-blockers and ARBs in MFS are scarce and inconsistent, with recent systematic and meta-analyses deeming no benefit of these medications in MFS patients 19,20 . However very recently, the AIMS trial has shown an association with a reduction in the rate of aortic dilation in MFS following treatment with the ARB irbesartan 21 . Despite a reduction in aortic root diameter rates, there is still an apparent overall increase in aortic root diameter over time.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, clinical data available on β-blockers and ARBs in MFS are scarce and inconsistent, with recent systematic and meta-analyses deeming no benefit of these medications in MFS patients 19,20 . However very recently, the AIMS trial has shown an association with a reduction in the rate of aortic dilation in MFS following treatment with the ARB irbesartan 21 . Despite a reduction in aortic root diameter rates, there is still an apparent overall increase in aortic root diameter over time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated recently that irbesartan significantly attenuated aortic root expansion in individuals with Marfan syndrome. 37 Conversely, ASO affords chronic and persistent inhibition of AGT synthesis to effect long-term depletion of angiotensin ligands. These durable effects of ASO enables inhibition of AGT synthesis to be tested as a possible approach to reduce TAA in Marfan syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, they demonstrated that ARB usage was associated with reduced aortic root growth in severely affected pediatric MFS patients. Multiple randomized controlled trials followed [129,130,[166][167][168][169][170][171] (Table 3). In 2013, the randomized open-label controlled COMPARE trial was published, which investigated the potential benefit of adding losartan to standard care, including a β-blocker in > 70% of the patients [129].…”
Section: Clinical Trials In Syndromic Taa Patientsmentioning
confidence: 99%
“…Also, this metaanalysis did not include the long-term follow-up study from the COMPARE trial [179]. Thus, when taking the results from the COMPARE, AIMS, and the long-term follow-up study of the COMPARE trial together, it seems that combining ARBs and β-blockers in MFS patients is not only preferential to prevent aneurysm growth but also to prevent long-term adverse outcomes [129,130,179].…”
Section: Arbs and β-Blockers: Synergy?mentioning
confidence: 99%